# l h LA = Lateral Surface Area l = length w = width h = height LA = 2(hw) + 2(lh) = 2( ) + 2( ) = ( ) + ( ) w.

## Presentation on theme: "l h LA = Lateral Surface Area l = length w = width h = height LA = 2(hw) + 2(lh) = 2( ) + 2( ) = ( ) + ( ) w."— Presentation transcript:

l h LA = Lateral Surface Area l = length w = width h = height LA = 2(hw) + 2(lh) = 2( ) + 2( ) = ( ) + ( ) w

LA = Lateral Surface Area  = 3.14 r = radius h = height LA = 2 r h = 2(3.14)( r )( h ) = 2(3.14)( )( )

LA = Lateral Surface Area  = 3.14 r = radius ℓ = Slant Height LA =  r ℓ = (3.14)( r )( ℓ ) = (3.14)( )( ) ℓ

LA = Lateral Surface Area s = side ℓ = Slant height LA = 2sℓ = 2( s )( ℓ ) = 2( )( ) ℓ s

s SA = Total Surface Area s = side (length of edge) SA = 6s² = 6(s) (s) = 6( ) ( )

l h SA = Total Surface Area l = length w = width h = height SA = 2(lw) + 2(hw) + 2(lh) = 2( ) + 2( ) + 2( ) = ( ) + ( ) + ( ) w

SA = Total Surface Area  = 3.14 r = radius r ² = (r)(r ) SA = 4  r ² = 4(3.14) ( r ) ( r ) = 4(3.14) ( ) ( )

SA = Total Surface Area  = 3.14 r = radius h = height SA = 2 r² + 2 rh = 2(3.14)(r)(r) + 2(3.14)(r)(h) = 2(3.14)( )( ) + 2(3.14)( )( ) = ( ) + ( )

SA = Total Surface Area  = 3.14 r = radius ℓ = Slant Height SA =  r² +  r ℓ = (3.14)(r)(r) + (3.14)(r)(ℓ) = (3.14)( )( ) + (3.14)( )( ) = ( ) + ( ) ℓ

SA = Total Surface Area s = side ℓ = Slant height SA = s² + 2sℓ = ( s )( s ) + 2( s )( ℓ ) = ( )( ) + 2( )( ) = ( ) + ( ) ℓ s

Download ppt "l h LA = Lateral Surface Area l = length w = width h = height LA = 2(hw) + 2(lh) = 2( ) + 2( ) = ( ) + ( ) w."

Similar presentations